The hypnotists - Korman, Gordon (New York : Scholastic Press, 2013)
Twelve-year-old Jackson Opus is descended from two powerful hypnotist bloodlines, but he has just begun to realize that he can control other peoples' actions with sometimes frightening results--especially when the head of the Sentia Institute plans to use Jackson for his own benefit.
750
3-6.
5.5.
Keywords: Hypnotism -- Juvenile fiction; Conspiracies -- Juvenile fiction; Paranormal fiction; Hypnotism -- Fiction; Conspiracies -- Fiction; Supernatural -- Fiction; Hypnotism -- Fiction; Conspiracies -- Fiction; Supernatural -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction